Where, exactly, is your farm? Syecomp's eFARMS farm-mapping service in Ghana - Allavi, Solomon Elorm; Coleman, Mary (Technical Centre for Agricultural and Rural Cooperation, 2017)
The company Syecomp offers a mapping service in Ghana for smallholder farmers. Farmers (or their organisations) call Syecomp, which puts them in touch with the local extension agent or a local lead farmer. This person visits the farm and walks around it with a hand-held global positioning device, recording the farm boundaries, individual fields, and the locations of features such as boreholes, streams, buildings and roads. He or she also notes the farmer’s name and contact details, and the types and varieties of crops grown.